Inventory of Pets and Natural Enemies on Cayenne Pepper Plants (Capsicum frutescens) in Larangan Slampar Village Pamekasan Regency - Sakinah, Ummu; Rachmania, Faridatul; Ali, Mahrus (Program Studi Biologi Fakultas Matematika dan IPA Universitas Annuqayah, 2024)
Chili plants are one of the important horticultural crops in Indonesia. There are many types of chili plants that are cultivated, one of which is cayenne pepper. However, there is one cause of less than optimal cayenne pepper production which is caused by pest attacks and plant diseases. The aim of this research is to determine the types of insects (pests) and natural enemies found on cayenne pepper plants. This research was conducted on 0.1 hectares of land which had been planted with chilies in Larangan Slampar Village, Tlanakan District, Pamekasan Regency. The research method used is exploratory descriptive. Insect sampling was carried out when the chili plants began to enter the generative period around 100 days after planting. The results of the research showed that the insect (pests) found on chili plants in the generative phase were the Order Hemiptera (Family: Cicadellidae and Aphididae) species Empoasca decipiens and Aphis gossypii Glover, as well as the Order Lepidoptera (Family Noctuidae) species Spodoptera litura F. Meanwhile, only one natural enemies were found. Order Hemiptera, (Family Cheilomenes) species C. sexmaculat.